2019
DOI: 10.1097/dcr.0000000000001324
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Versus No Antibiotics for Acute Uncomplicated Diverticulitis: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: Antibiotics are routinely used for diverticulitis irrespective of severity. Current practice guidelines favor against the use of antibiotics for acute uncomplicated diverticulitis. OBJECTIVE: We performed a systematic review and meta-analysis to examine the role of antibiotic use in an episode of uncomplicated diverticulitis. DATA SOURCES: PubMed/Medline, Embase, Scopus, and Cochrane were used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 26 publications
1
21
0
2
Order By: Relevance
“…]in patients with uncomplicated diverticulitis. Five meta-analyses (including RCTs, cohort studies and case-control studies)[174][175][176][177][178] [Au: removed information on publication year for brevity] demonstrated that clinical outcomes between patients treated with and those treated without antimicrobials are not substantially different. Indeed, no substantial differences were evident in the proportion of patients requiring additional treatment or intervention, rate of readmission or deferred admission, need for surgical or radiological intervention, and recurrence or complication rate.…”
mentioning
confidence: 99%
“…]in patients with uncomplicated diverticulitis. Five meta-analyses (including RCTs, cohort studies and case-control studies)[174][175][176][177][178] [Au: removed information on publication year for brevity] demonstrated that clinical outcomes between patients treated with and those treated without antimicrobials are not substantially different. Indeed, no substantial differences were evident in the proportion of patients requiring additional treatment or intervention, rate of readmission or deferred admission, need for surgical or radiological intervention, and recurrence or complication rate.…”
mentioning
confidence: 99%
“…The first statements are dedicated to the current indication on antibiotic of in the setting of AD. The first claims that the management of acute diverticulitis without antibiotics does not increase these worse outcomes [63][64][65][66][67][68]. Therefore, the second statement confirms that antibiotics have to be used by a "case-by-case" basis [5,66], and that some parameters (namely levels of PCR and CT findings at entry) may be predictive on the need to use antibiotics in this population (48,66).…”
Section: Commentsmentioning
confidence: 89%
“…92'9 % of the patients in 2019 were classified as Hinchey I It is a disease that can range from mild to potentially severe, depending on which its treatment may vary. For a long time, antibiotic treatment has been the treatment of choice for mild acute diverticulitis; however, some studies have shown that dietary changes alone can resolve it p [8,9]. In our study, we can observe how the number of consultations of mild patients decreased without a very significant increase in the number of consultations of severe cases.…”
Section: Resultsmentioning
confidence: 52%